Role of Strain-Hardening Law on the Bursting Speed of a Rotating Thin-Walled Shaft - Guven, U. (SPRINGER, 2009)
In the present work, the bursting speed of a rotating thin-walled shaft is considered. Under usual assumptions, the roles of modified Ludwik and Ramberg-Osgood stress-strain laws on the bursting speed are discussed. It can be seen from the present analysis that the strain hardening law plays a significant role.
Keywords: Materials Science; Metallurgy & Metallurgical Engineering